(untitled) (Bangladesh Medical Journal, 2024)
Hepatic encephalopathy is a broad spectrum neuropsychiatric abnormalities of liver dysfunction. Ammonia level may correlate with the severity of liver failure. The brain is very sensitive to the toxic effects of ammonia. As a result patient may manifests with irritability, slurring of speech, reversal of sleep-awake cycle, flapping tremor, confusion, stupor or even deep coma. This study was aimed to validate the ammonia level in children with liver failure for the assessment of its severity considering hepatic encephalopathy. This cross-sectional comparative study was conducted among 64 children aged 1-15 years of both sexes (study subjects) diagnosed as acute or acute on chronic liver failure in the Department of Pediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period of November 2017 to September 2019. The subject were divided into two groups for the comparison of ammonia level to assess the severity in contrast to hepatic encephalopathy. In the first group 32 were liver failure with encephalopathy and in the second group 32 were liver failure without encephalopathy. Hepatic encephalopathy was diagnosed on the basis of West Haven Criteria. The analysis was done by the Receiver Operating Characteristic Curve with SPSS-20. Among the 64 patients female were 45% whereas male patients were 55%, male female ratio was 1.2: 1. Regarding etiology, Wilson disease was the most common cause and it was nearly two-third (65.6%) of children, cryptogenic cirrhosis was 10%, Hepatitis A was 9.4%, Autoimmune Hepatitis (AIH) was 3.10%, Hepatitis E, Hepatitis B, Hepatitis C, biliary atresia and lipid storage were 1.60% respectively. This study showed that, ammonia of ≥71 µmol/L is an indicator for presence of hepatic encephalopathy in children. The analysis by the Receiver Operating Characteristic Curve showed area under the curve (AUC) is 0.86 with upper bound 0.96 and lower bound is 0.77. It was observed that about half (48.4%) of the children had positive blood ammonia level (≥71.0 umol/L) and among the children of positive blood ammonia level most of them (80.65%) had hepatic encephalopathy and 19.35% had no encephalopathy. More than half (51.6%) children had negative (<71.0 umol/L) blood ammonia level, among them 21.21% children had encephalopathy and 78.79% patients had no encephalopathy. Sensitivity of blood ammonia was found 78.1%, specificity 81.2%, positive predictive value 80.6%, negative predictive value 78.8% and accuracy 79.7%. In conclusion, high level of ammonia is found with higher grade of encephalopathy and hyperammonia is also found in liver failure without encephalopathy. Bangladesh Med J. 2023 May; 52(2): 1-5